Efficacy and safety of using a unilateral lower limb exoskeleton combined with conventional treatment in post-stroke rehabilitation: a randomized controlled trial - Jin, Ying; Xiong, Bing; Chen, Lina; Zhao, Weiwei; Li, Zhe; Zhang, Chi; Xu, Xin (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: The incidence of hemiplegia caused by stroke is high. In particular, lower limb dysfunction affects the daily activities of patients, and lower limb robotic devices have been proposed to provide rehabilitation therapy to improve balance function in this patient population. Objective: To assess the effectiveness of the LiteStepper® unilateral lower limb exoskeleton (ULLE) combined with conventional treatment for balance function training in patients with post-stroke hemiplegia. Methods: This multicenter randomized controlled trial, conducted in the convalescent rehabilitation ward of four hospitals, involved 92 patients in their post-stroke phase. Participants were randomized into an experimental group (EG) or a conventional group (CG). The EG adopted the LiteStepper® ULLE combined with conventional treatment for 21 days. The CG underwent a standard daily rehabilitation routine for 21 days. The Berg Balance Scale (BBS), Functional Ambulation Category scale (FAC), 6-min walk test (6MWT), and Barthel Index (Barthel) were used for evaluations before and after 21 days of rehabilitative training. Results: The BBS scores in EG was significantly elevated compared to CG, exhibiting a profound statistical difference (P<0.0001). Notably, these disparities persisted at both day 21 (P < 0.0001) and day 14 (P < 0.0047) post-intervention, underscoring the efficacy of the treatment in the EG. The EG demonstrated a markedly greater improvement in BBS scores from pre-rehabilitation to 21 days post-training, significantly outperforming the CG. Furthermore, at both day 14 and day 21, functional assessments including the FAC, 6MWT, and Barthel revealed improvements in both groups. However, the improvements in the EG were statistically significant compared to the CG at both time points: day 14 (FAC, P = 0.0377; 6MWT, P = 0.0494; Barthel, P = 0.0225) and day 21 (FAC, P = 0.0015; 6MWT, P = 0.0005; Barthel, P = 0.0004). These findings highlight the superiority of the intervention in the EG in enhancing functional outcomes. Regarding safety, the analysis revealed a solitary adverse event (AEs) related to the LiteStepper®ULLE device during the study period, affirming the combination therapy's safety profile when administered alongside conventional balance training in post-stroke hemiplegic patients. This underscores the feasibility and potential of incorporating LiteStepper®ULLE into rehabilitation.